PENERAPAN CRITICAL CONTROL POINT DAGING RENDANG DI RUMAH MAKAN PADANG TERHADAP NILAI pH DAN MUTU RASA ORGANOLEPTIK - Narastyawan, Anggoro Rizky; Pramono, Yoyok Budi; Dwiloka, Bambang (Journal of Agritechnology and Food Processing, 2021)
This study aims to compare the production process of rendang at Padang restaurants and the production of rendang itself, namely by observing CCP management in the running production process or not. Observation of the implementation of CCP management was carried out on the pH value and organoleptic values. This study conducted observations on the implementation of CCP management in the rendang production process in Padang restaurants then carried out the production of rendang itself by implementing CCP management and made improvements in the production process so that rendang was analyzed for pH value and organoleptic. The research data were analyzed using the Independent Sample T Test. Data analysis on the organoleptic test used the non-parametric Kruskal Wallis test and continued with the Mann Whitney test. The results of this study indicate that the rendang that is produced by CCP management is better than the rendang produced in Padang restaurants because it does not apply CCP management and has a significant effect (P <0.05) so it has poor test results. The results showed that padang restaurants needed to take corrective action on their tighter production processes so that their food products would be better.